2012
DOI: 10.1128/aac.05100-11
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Inhibits Porphyromonas gingivalis Proteinases and Has Sustained Biofilm Inhibitory Activity

Abstract: Porphyromonas gingivalis is a bacterial pathogen associated with chronic periodontitis that results in destruction of the tooth's supporting tissues. The major virulence determinants of P. gingivalis are its cell surface Arg-and Lys-specific cysteine proteinases, RgpA/B and Kgp. Lactoferrin (LF), an 80-kDa iron-binding glycoprotein found in saliva and gingival crevicular fluid, is believed to play an important role in innate immunity. In this study, bovine milk LF displayed proteinase inhibitory activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 55 publications
(53 reference statements)
1
39
0
1
Order By: Relevance
“…In addition, we have shown that the expression of these genes was downregulated in a P. gingivalis ferric uptake regulator (Fur) orthologue knockout mutant (unpublished observation). We have also shown that heme-limited P. gingivalis has reduced biofilm-forming capacity compared with P. gingivalis grown under excess heme conditions (51). It is therefore possible that at the sub-MIC used in this study, the oxantel inhibition of Frd activity reduced energy levels in the cell, which then acted as a weak inducer of a subset of genes of this regulon.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we have shown that the expression of these genes was downregulated in a P. gingivalis ferric uptake regulator (Fur) orthologue knockout mutant (unpublished observation). We have also shown that heme-limited P. gingivalis has reduced biofilm-forming capacity compared with P. gingivalis grown under excess heme conditions (51). It is therefore possible that at the sub-MIC used in this study, the oxantel inhibition of Frd activity reduced energy levels in the cell, which then acted as a weak inducer of a subset of genes of this regulon.…”
Section: Discussionmentioning
confidence: 95%
“…23) However, a few reports indicated that CMP could influence the virulence of foodborne pathogens including biofilm formation. Recent studies have indicated that several milk peptides, including osteopontin 24) and lactoferrin, 25) strongly reduced the amount of dental biofilm. We indicated here that CMP would be potentially useful in preventing biofilm formation on PVC and glass surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…These concentrations correspond to those required for the inhibition of Rgp activity. Such agents as cranberry polyphenol 28,29) and lactoferrin 46) have also demonstrated inhibitory activities against both biofilm formation and Rgp/Kgp activity. However, in the case of cranberry polyphenol and lactoferrin, the concentration required for inhibiting biofilm formation was inconsistent with that required for inhibiting the proteinase activities.…”
Section: Discussionmentioning
confidence: 99%